2015
DOI: 10.20344/amp.5562
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Autonomic Dysfunction in Patients with Multiple Sclerosis

Abstract: (1):51-55 RESUMOIntrodução: A disfunção do sistema nervoso autónomo é comum na esclerose múltipla e deveria ser explorada na avaliação de rotina. O questionário Composite Autonomic Symptom Score foi validado como instrumento de auto-avaliação de sintomas autonómicos. Objetivos: Determinar a frequência de sintomas autonómicos em doentes com esclerose múltipla através de uma versão portuguesa do Composite Autonomic Symptom Score; comparar os resultados do questionário entre um grupo de doentes e um grupo control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
2
10
0
1
Order By: Relevance
“…Concerning the frequency of DS, we have shown that, using the COMPASS-31 questionnaire in adults, subtle ANS impairment in at least 1 domain is present in the majority (> 98%) of subjects, independently from the diagnosis of MS. On the contrary, the presence of a score > 0 in ≥ 2 domains was more common in MS patients compared with HC (94.8% vs. [15]. The most frequently involved domain in our MS population was the GI (90.7%).…”
Section: Discussionmentioning
confidence: 67%
“…Concerning the frequency of DS, we have shown that, using the COMPASS-31 questionnaire in adults, subtle ANS impairment in at least 1 domain is present in the majority (> 98%) of subjects, independently from the diagnosis of MS. On the contrary, the presence of a score > 0 in ≥ 2 domains was more common in MS patients compared with HC (94.8% vs. [15]. The most frequently involved domain in our MS population was the GI (90.7%).…”
Section: Discussionmentioning
confidence: 67%
“…The main clinical symptoms connected with cardiovascular autonomic neuropathy are fatigue [ 59 , 60 ] and pathological responses to orthostatic challenge such as syncope, palpitation, dizziness, nausea, general weakness, hot flashes and sweating [ 61 , 62 , 63 , 64 , 65 , 66 ]. Symptoms associated with orthostatic dysregulation occur in up to 63% of the patients [ 61 , 62 , 63 , 64 , 65 , 66 ]. Postural orthostatic tachycardia syndrome (POTS), vasovagal syncope and orthostatic hypotension can be induced by tilt table test in MS patients [ 64 ].…”
Section: Cardiovascular Dysregulationmentioning
confidence: 99%
“…The area of bowel dysfunction is considered the “Cinderella” of MS research, although 40%–81% of the patients complain about functional loss in the gastrointestinal domain [ 66 , 105 ]. The most frequently reported gastrointestinal (GI) symptoms encompass anorectal dysfunction characterized by constipation (37%–68%) [ 105 , 106 ], fecal incontinence (15%–51%) [ 105 , 107 ] or the combination of these (23%) [ 108 ] and deglutitive problems such as dysphagia (21%) [ 105 ].…”
Section: Gastrointestinal Dysregulationmentioning
confidence: 99%
“…Autonomic dysfunction is common in patients with MS and affects the quality of life of patients 27 . Autonomic dysfunction affects the bowel, bladder and sexual functions as well as the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%